Prevalence of Diseases in Broilers Age Group 1-14 Days at Chitwan District, Nepal - Subedi, Deepak; Kandel, Milan; Khanal, Shrijana; Mahato, Prem Lal; Acharya, Ramchandra (International Journal of Applied Sciences and Biotechnology, 2020)
This study was undertaken to find out the prevalence of diseases in broilers age group 1-14 days at Chitwan district, Nepal. This subjective study was carried out using the secondary data retrieved from National Avian Disease Investigation Laboratory (NADIL). Chitwan and Veterinary Teaching Hospital (VTH), Agriculture and Forestry University (AFU), Rampur, Chitwan in last two years viz. June 2016 to June 2018. The cases recorded were categorized and those up-to age 14 days old broiler chicks (n=1112) were selected for the study. Data and Informations were entered in Microsoft Excel 2010 and analyzed using SPSS ver. 22. Results illustrates that the average flock size was 913.51± 918.49 with a range from 30 to 10000 chicks. The case was reported highest in 14th day followed by 12th and 10th day. The prevalence of bacterial disease was found to be highest (57.46%) followed by mycoplasma infection (10.61%) and metabolic diseases (10.16%). Prevalence of Colibacillosis was highest (43.25%) followed by Salmonellosis (12.85%) and Chronic Respiratory Disease (CRD) (10.61%). The level of chicks’ average mortality was 2.14% of total flock size. The Pearson’s correlation between flock size and mortality was found to be 0.82, which was highly significant (p